Socially responsible investment by generation Z: a cross-cultural study of Taiwanese and American investors. Issue 3 (3rd April 2019) - Chen, Mei-Hua; Chen, Bryan H.; Chi, Christina Geng-qing
ABSTRACT: This study used Hofstede's cultural dimensions theory to examine Generation Z investors' socially responsible investment perceptions, utilizing data collected from Taiwan and the United States. Generation Z is the most global and socially empowered generation in history, and whether social responsibility appeals to Generation Z warrants investigation. Of 412 questionnaires collected in the United States, 380 were usable, and of 475 collected in Taiwan, 439 were usable. This study exained four variables, namely nationality, gender, work experience, and share ownership; these variables affected how the participants in this study understood and accepted the concept of socially responsible investment. These results provide interesting insight into Generation Z's pro-social attitudes, Perceived consumer effectiveness and trust. This paper suggests implications for cross-cultural study theory and practice, as well as future research directions.